2017
DOI: 10.1113/ep086417
|View full text |Cite
|
Sign up to set email alerts
|

Central angiotensin‐(1–7) increases osmotic thirst

Abstract: What is the central question of this study? The central goal of this study was to understand the effects of central angiotensin-(1-7) on basal and osmotically stimulated water intake in rats. What is the main finding and its importance? This study demonstrated that central administration of angiotensin-(1-7) did not induce thirst in basal conditions but increased water intake after osmotic stimulation, such as water deprivation and salt loading. These results indicate a new function for this peptide, which, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…ACE2 also play an important role to maintain fluid and electrolyte balance, because ACE2 changes Ang II to Ang-(1-7) (Cohen et al 2020). Additionally, Dos-Santos et al (2017) showed that intracerebroventricular injection of Ang-(1-7) increased water intake after osmotic stimulates. Furthermore, SARS-CoV-2 induces downregulation of ACE2 expression and shedding from the cell surface, resulting in an increase of Ang II and a decrease of Ang-(1-7) (Cohen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACE2 also play an important role to maintain fluid and electrolyte balance, because ACE2 changes Ang II to Ang-(1-7) (Cohen et al 2020). Additionally, Dos-Santos et al (2017) showed that intracerebroventricular injection of Ang-(1-7) increased water intake after osmotic stimulates. Furthermore, SARS-CoV-2 induces downregulation of ACE2 expression and shedding from the cell surface, resulting in an increase of Ang II and a decrease of Ang-(1-7) (Cohen et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SARS-CoV-2 induces downregulation of ACE2 expression and shedding from the cell surface, resulting in an increase of Ang II and a decrease of Ang-(1-7) (Cohen et al 2020). These suggest that serum electrolyte balance is affected by COVID-19, although the effect of Ang-(1-7) on serum electrolytes is unclear (Dos-Santos et al 2017). Lippi et al (2020) found that the levels of sodium, potassium, and calcium in severe COVID-19 patients were significantly higher than those in non-severe patients.…”
Section: Introductionmentioning
confidence: 99%
“…Joyner et al [69] using intravenous infusion of the MAS antagonist, A779, in pregnant rats suggested that Ang-(1-7) contributes to enhance water intake during pregnancy. In addition, dos Santos et al [70] showed that after water deprivation or salt loading, ICV Ang-(1-7) increased water intake. The expression of MAS in the parvocellular area of PVN and in other nuclei that control water intake [1,39] form the basis to support a dipsogenic effect of Ang-(1-7), at least in particular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, angiotensin-converting enzyme 2, as a carboxymonopeptidase, catalyzes angiotensin II conversion to angiotensin 1-7. Previous studies have reported that angiotensin 1-7 doesn't induce thirst in basal conditions but increased water intake after osmotic stimulation, such as water deprivation and salt loading in rats (Dos-Santos et al 2017). The positive selected ACE2 may implicit that A. latus could maintain the osmotic and cell volume homeostasis by regulating the activity of ACE2.…”
Section: Evolution Of Gene and Gene Families For Salinity Tolerancementioning
confidence: 96%